Achieving homogeneous distribution of high-content graphene in aluminum alloys via high-temperature cumulative shear deformation. (August 2020) - Zheng, Zhong; Zhang, Xuexi; Li, Jianchao; Geng, Lin
Abstract: Homogeneous dispersion of high-content graphene nano-platelet (GNP) in metals is challenging due to the serious aggregation tendency of graphene. Traditional secondary processing such as extrusion usually has too limited shear strains to reach a desirable GNP dispersion state. Our previous work demonstrated that 1.0 vol% GNP/Al composite was successfully produced via multiple wire-drawing at ambient temperature. However, the fabrication of 5.0 vol% GNP/Al composite was not successful because of the limited cumulative shear strains. Here we described fully dispersed state of 5.0 vol% GNP in Al by hot-drawing at an elevated temperature 400 °C. The evolution of the microstructures and mechanical properties were investigated in relation to the number of drawing passes. The ultra-fine grains with size 372 nm were obtained via dynamic recrystallization after drawing for six passes (cumulative strain 94%). In particular, stripping of the GNP into thin layers and their preferential alignment in the wire axis occurred during the shear deformation. As a result, 5.0 vol% GNP/Al composite produced by six-pass drawing possessed improved yield strength ( σ s, 449 MPa) and ultimate tensile strength (UTS, 461 MPa). The results demonstrated the feasibility of dispersing high-content GNP in aluminum alloys by extrusion followed by multi-pass hot drawing techniques. Graphical abstract: Unlabelled Image Highlights: Distribution of GNP in 5 vol% GNP/Al composite was studied during multi-pass hot drawing. The microstructural evolution of GNP/Al composite during multi-pass hot drawing was investigated. vol% GNP was homogeneously distributed in Al matrix with ultra-fine grains structures after six-passes drawing. The yield strength and ultimate tensile strength of six-passes drawn composite reached 449 MPa and 461 MPa, respectively.